Association Between Safety Culture and Students' Compliance with Laboratory Safety Procedures - Asran; Irwan Amar (Jurnal Ilmu Kesehatan Nusantara, 2024)
Background: Safety culture is a fundamental element in creating a safe learning environment within higher education institutions, particularly for students engaged in laboratory and practical activities. A positive safety culture is expected to improve compliance with safety procedures and reduce the risk of accidents during academic practice. Research Objective: This study aimed to analyze the association between safety culture and students' compliance with safety procedures among undergraduate students at the Institute of Technology and Health Sciences (ITEKES) Tri Tunas Nasional Makassar. Methods: A quantitative analytical study with a cross-sectional design was conducted among 96 undergraduate students from the Bachelor of Occupational Safety Engineering, Bachelor of Nutrition, and Bachelor of Hospital Administration programs. Respondents were selected using proportionate stratified random sampling. Data were collected using validated self-administered questionnaires measuring safety culture and compliance with safety procedures. Descriptive statistics were used to summarize respondent characteristics, while the Chi-square test was performed to determine the association between study variables, with a significance level of p < 0.05. Results: Most respondents demonstrated a good safety culture (63.5%) and were compliant with safety procedures (70.8%). Chi-square analysis revealed a statistically significant association between safety culture and compliance with safety procedures (p < 0.001). Students with a good safety culture showed substantially higher compliance (83.6%) than those with poor safety culture (48.6%). Conclusion: Safety culture was significantly associated with students' compliance with safety procedures. Strengthening institutional safety culture through continuous education, laboratory supervision, safety training, and policy implementation is essential to promote safe behavior and enhance occupational safety practices in higher education institutions.